Results of the European EDITH nephrologist survey on factors influencing treatment modality choice for end-stage kidney disease. Issue 1 (22nd January 2021) - de Jong, Rianne W; Jager, Kitty J; Vanholder, Raymond C; Couchoud, Cécile; Murphy, Mark; Rahmel, Axel; Massy, Ziad A; Stel, Vianda S
Abstract: Background: Access to forms of dialysis, kidney transplantation (Tx) and comprehensive conservative management (CCM) for patients with end-stage kidney disease (ESKD) varies across European countries. Attitudes of nephrologists, information provision and decision-making may influence this access and nephrologists may experience several barriers when providing treatments for ESKD. Methods: We surveyed European nephrologists and kidney transplant surgeons treating adults with ESKD about factors influencing modality choice. Descriptive statistics were used to compare the opinions of professionals from European countries with low–, middle– and high–gross domestic product purchasing power parity (GDP PPP). Results: In total, 681 professionals from 33 European countries participated. Respondents from all GDP categories indicated that ∼10% of patients received no information before the start of renal replacement therapy (RRT) (P = 0.106). Early information provision and more involvement of patients in decision-making were more frequently reported in middle- and high-GDP countries (P < 0.05). Professionals' attitudes towards several treatments became more positive with increasing GDP (P < 0.05). Uptake of in-centre haemodialysis was sufficient to 73% of respondents, but many wanted increased uptake of home dialysis, Tx and CCM. Respondents experienced different barriers according to availability of specific treatments in their centre. The occurrence of barriers (financial, staff shortage, lack of space/supplies and patient related) decreased with increasing GDP (P < 0.05). Conclusions: Differences in factors influencing modality choice when providing RRT or CCM to adults with ESKD were found among low-, middle- and high-GDP countries in Europe. Therefore a unique pan-European policy to improve access to treatments may be inefficient. Different policies for clusters of countries could be more useful.